1998
DOI: 10.1021/jm970704s
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Binding Mode of Teleocidin and Benzolactams to the Cys2 Domain of Protein Kinase Cδ by Synthesis of Hydrophobically Modified, Teleocidin-Mimicking Benzolactams and Computational Docking Simulation

Abstract: Phorbol esters (12-O-tetradecanoylphorbol 13-acetate; TPA) and teleocidins are known to be potent tumor promoters and to activate protein kinase C (PKC) by binding competitively to the enzyme. The relationship between the chemical structures and the activities of these compounds has attracted much attention because of the marked structural dissimilarities. The benzolactam 5, with an eight-membered lactam ring and benzene ring instead of the nine-membered lactam ring and indole ring of teleocidins, reproduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…In addition, the lower Ki value of ILV (34) compared to compound 38 (80 and 1700 nM, respectively) was explained by CH/π interactions between the indole ring in ILV and Pro241 in PKCδ [135,140].…”
Section: Structure-activity Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, the lower Ki value of ILV (34) compared to compound 38 (80 and 1700 nM, respectively) was explained by CH/π interactions between the indole ring in ILV and Pro241 in PKCδ [135,140].…”
Section: Structure-activity Studiesmentioning
confidence: 95%
“…The structurally simplest member of the family is (-)-indolactam V (ILV, 34), which can be produced in large quantities in Actinomycetes and has therefore been used as a starting point for the synthesis of new derivatives [58]. Several groups -the Irie, the Kozikowski, and the Endo groups -have carried out research into these compounds, revealed important structure-activity relationships and developed novel indolactam and benzolactam derivatives with improved selectivity profiles (see, for example, [133][134][135]). …”
Section: Indo-and Benzolactamsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Although 12-epi-PDBu, 85 ingenol 3-benzoate, 86 (À)-indolactam-V (ILV), 87,88 5-prenyl-ILV, 89 (3R)-indolinelactam-V (ILLV), 90 8 or 9-decylbenzolactam-V8 (BLV8), [91][92][93] bound selectively to the C1B domain of PKCd [ratio: K i (C1A)/ K i (C1B)450], 9-decyl-benzolactone-V8 (BLnV8), 94 thio-ILV, 95 and aplysiatoxin (ATX) 96,97 showed less preference for the C1B domain comparable to bryo-1 (ratio: 8.8). Especially, ATX and its artificial derivative 3-O-Me-ATX displayed an unexpected binding preference (ratio: 29 and 19, respectively), with the potent binding affinity at the nanomolar level.…”
Section: Attempts To Develop New Anticancer Drugs Based On the Skeletmentioning
confidence: 99%
“…In addition, one of the carbonyl groups of the template forms a hydrogen bond with a backbone amide proton as the C3 carbonyl of phorbol-13-O-acetate. phorbol esters, DAGs and benzolactams and derivatives of them are thought to interact with either the hydrophobic amino acids surrounding the ligand binding cleft or with the hydrophobic moiety in the lipid bilayer [17,22,23]. Also hydrophobic interactions of ligands are important for high-affinity binding to the protein.…”
Section: Design and Structure-activity Relationship Of Novel C1 Domaimentioning
confidence: 99%